2014
DOI: 10.1007/s12013-014-9945-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Hispidulin, Genistein, and Icariin with Estrogen on Bone Tissue in Ovariectomized Rats

Abstract: Icariin, Genistein, and Hispidulin have been proven to have estrogen-like and antiosteoporotic activity and can be potentially used for the treatment of osteoporosis. The present study found that Icariin, Genistein, and Hispidulin treatments, emulating estrogen, significantly contributed to bone density. Comparative effects of Icariin, Genistein, and Hispidulin with estrogen on in ovariectomized rats were investigated. Our results showed that genistein was found to have superior bone protective effects against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Icariin has been identified as an inhibitor of cathepsin K and may suppress cartilage and bone degradation in mice with collagen-induced arthritis ( 13 ). In vivo , icariin has demonstrated significant anti-osteoporosis effects in ovariectomized rats and mice, glucocorticoid-induced rats and OPG knockout mice ( 7 , 8 ). However, in vitro studies have indicated that icariin may reduce TRAP activity and increase osteogenic differentiation, calcium deposition and mineralized nodule formation in induced bone marrow stromal and RAW264.7 cells ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Icariin has been identified as an inhibitor of cathepsin K and may suppress cartilage and bone degradation in mice with collagen-induced arthritis ( 13 ). In vivo , icariin has demonstrated significant anti-osteoporosis effects in ovariectomized rats and mice, glucocorticoid-induced rats and OPG knockout mice ( 7 , 8 ). However, in vitro studies have indicated that icariin may reduce TRAP activity and increase osteogenic differentiation, calcium deposition and mineralized nodule formation in induced bone marrow stromal and RAW264.7 cells ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Icariin has been identified as a flavonoid isolated from Herba Epimedii ( Epimedium brevicornum ), which is the most commonly used Chinese herbal medicine in the treatment of sexual dysfunction and osteoporosis ( 5 , 6 ). The anti-osteoporotic role of icariin has been verified in ovariectomized rats ( 7 , 8 ) and glucocorticoid-induced osteoporotic rats ( 9 ). A 24-month randomized double-blind placebo-controlled clinical trial indicated that an Epimedium -derived phytoestrogen flavonoid preparation containing 60 mg icariin, 15 mg daidzien and 3 mg genistein was able to limit bone loss in late postmenopausal women ( 10 ).…”
Section: Introductionmentioning
confidence: 97%
“…Hispidulin have been proven to have estrogen-like and antiosteoporotic activity and can be potentially used for the treatment of osteoporosis 23 . Effect of hispidulin on ovariectomy (OVX)-induced bone loss in mice was investigated.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Wei et al found that icariin could promote bone formation, increase trabecular numbers, and reduce trabecular separation [23]. The comparing study showed that there was no obvious difference between icariin and estrogen on anti-osteoporotic activity in OVX rats [24]. The main bioactive components of this herb are prenylated flavonol glycosides, and the absorption of flavonol glycosides increased, while the number of glucosides decreased [25,26].…”
mentioning
confidence: 99%